Rapid environmental changes in the Lake Qinghai basin during the late Holocene - Wang, Chen; Qiu, Yahui; Fan, Fenglei; Li, Baosheng; Niu, Dongfeng; Shu, Peixian (Frontiers in Earth Science, 2023)
The Lake Qinghai Basin is sensitive to global and regional climate change because of its unique geographical location. It is the hotspot for paleoclimate research in East Asia. In this study, we reconstructed the environmental evolution of the Lake Qinghai since ~9 ka by using a high-resolution peat and fluvial-lacustrine record (LYG profile) obtained at the foot of Nanshan Mountain. Based on 8 AMS14C dates and lithology, loss on ignition (LOI), total organic matter (TOC), X-ray fluorescence (XRF) core-scanning measurements, ratio of total organic carbon to nitrogen (TOC/TN), and sediment particle sorting coefficients, we show that during the Middle Holocene (~9-4.4 ka BP) this region was primarily dominated by the Asian summer monsoon, with a consistent, warm, and humid environment. By contrast, during the late Holocene (4.4 ka to present), the climatic context in this area fluctuated dramatically at the millennial scales. The low TOC content, lower TOC/TN ration and strong hydroclimatic indicate six rapid climate change events, which occurred at ~4.0 ka, ~3.6 ka, ~3.2 ka, ~2.8 ka, ~2.1 ka, and ~1.4 ka, all of which coincided to cold episodes in the North Atlantic Ocean.